Assessing Inquiry Skills of High School Students - Ješková, Zuzana; Lukáč, Stanislav; Šnajder, Ľubomír; Guniš, Ján; Balogová, Brigita; Kireš, Marián (Scientia in educatione, 2016)
Inquiry-based science education (IBSE) has become recently one of the most used terms with regard to innovation of science education. The main goal of IBSE is not only conceptual understanding but also development of students’ skills to conduct inquiry and evaluate gained results. The presented research is aimed at diagnosing the current status of selected inquiry skills’ development of high school students. Based on the existing tests and the inventory of inquiry skills a test of inquiry skills was developed. The test items that intend to assess the level of the skills to design experiment (identify variables and their relationship), transform results into graph, determine relationships, identify possible sources of errors and defend results and form arguments, are situated in the context of mathematics, physics or informatics. The test was taken by 751 students from 1st or 2nd grade classes of several Slovak high schools. The quantitative analysis of test results showed low level of gained score in the whole test (average value of 32.5 %) as well as in particular test items (in the range of 8–50 %, approx.). Detailed qualitative analysis revealed many student diï¬culties that were most signiﬁcant in the ﬁeld of analysis and interpretation skills and skills to defend results and form arguments.